Influence of Fiber Type on Fatigue Performance of Fiber-Reinforced Inlay-Retained Dental Prostheses - Szabó, Veronika T.; Mészáros, Csongor; Szabó, Balázs; Szabó P., Balázs; Braunitzer, Gábor; Palkovics, Dániel; Geretovszky, Zsolt; Säilynoja, Eija; Lassila, Lippo; Garoushi, Sufyan; Fráter, Márk (Elsevier, 2026)
Objectives
To assess the effect of using only long- and short-glass fibers or their combination on the fatigue resistance of composite inlay-retained dental prostheses in dissected mandibular molars with different levels of periodontal support.
Materials and Methods
Seventy-two mandibular first molars and second premolars were included in our study. Distal halves of extracted molars were kept, and received endodontic treatment. Standardized occluso-distal and mesio-occlusal cavities were prepared, and premolar-molar units were assembled. The edentulous spans were restored by direct inlay-retained composite prostheses fabricated in 3 different ways (n = 12, 6 groups). In groups 1A and 1B, long fibers and a packable composite, in groups 3A and 3B, short fibers, while in groups 2A and 2B both short and long fibers were used. All units were embedded simulating either physiological periodontal support (1A-3A) or furcation involvement (1B-3B). Specimens were subjected to accelerated fatigue-testing through 40,000 cycles or until fracture. Kaplan–Meyer survival analysis and factorial ANOVA were conducted. Fracture mode was evaluated visually and by scanning electron microscopy.
Results
Group 2A (mean 39106.00 N, SD ± 2451, survival frequency 83.3%) and 2B (mean 38454.33 N, SD ± 3110, survival frequency 75%) had the highest load-bearing capacity. Factorial ANOVA revealed that the restorative material significantly affected load-bearing capacity (P < .05) regardless of the periodontal support.
Conclusion
The combination of long and short fiber-reinforced systems significantly enhanced the fatigue resistance of direct inlay-retained composite prosthesis.
Clinical relevance
This approach may counterbalance the weakening effects of impaired periodontal support, thus improving treatment outcomes for patients with compromised molar support.